2017
DOI: 10.1111/liv.13523
|View full text |Cite
|
Sign up to set email alerts
|

Weighing the risks: Morbid obesity and diabetes are associated with increased risk of death on the liver transplant waiting list

Abstract: Morbid obesity and diabetes are independent predictors of death in LT candidates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 31 publications
3
42
0
3
Order By: Relevance
“…Currently, NASH‐related cirrhosis is frequently missed as a diagnosis with the consequence of presenting with more advanced liver disease and HCC, thereby limiting potential curative options including transplantation . In addition, with the increasing prevalence of metabolic factors (diabetes, overweight, or obesity), which have a negative impact on wait‐list dropout rates and survival after LT, strategies to optimize weight and diabetes control and avoid sarcopenia should be prioritized in these patients within LT programs.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, NASH‐related cirrhosis is frequently missed as a diagnosis with the consequence of presenting with more advanced liver disease and HCC, thereby limiting potential curative options including transplantation . In addition, with the increasing prevalence of metabolic factors (diabetes, overweight, or obesity), which have a negative impact on wait‐list dropout rates and survival after LT, strategies to optimize weight and diabetes control and avoid sarcopenia should be prioritized in these patients within LT programs.…”
Section: Discussionmentioning
confidence: 99%
“…(8,9) Class III obesity, in particular, has been found to be a risk factor for mortality among those awaiting liver transplantation (LT), according to two recent United Network for Organ Sharing (UNOS) registry studies. (10,11) In a recent study by Piano et al, several predictors of ACLF development were identified, including ascites, anemia, hypotension and increasing model for end-stage liver disease (MELD) score. (12) However, this study did not include obese patients, as the upper limit of body mass index (BMI) in their study population was 29 kg/m 2 .…”
Section: Introductionmentioning
confidence: 99%
“…A similar observation has also been reported in a recent analysis for both LT alone and liver-kidney recipients. 25,26 While this study is not designed to provide rigorous evaluation of the reasons behind these outcome differences, they certainly merit further study.…”
Section: Characteristics Of Lt Recipients With Bashmentioning
confidence: 99%